Pulses of the Electromagnetic Field with a Non-Zero Electric Area - Plachenov, A. B.; Rosanov, N. N. (Radiophysics and quantum electronics, 2023)
We analyze the possibility of existence of electromagnetic-field pulses with a non-zero electric area (time integral of the electric field) within the framework of the Maxwell equations. It is demonstrated that in the absence of charges and currents in vacuum, the non-zero electric area of a pulse would lead to its infinite energy. A pulse with the non-zero area is shown to form already in the case of uniform and rectilinear motion of the charge. The conditions for formation of such pulses by a localized charge system are found, and an example of such a system is presented. The asymptotics of the electric area far from the system of charges is obtained.